The impact of intergenerational transfers on household wealth inequality in Japan and the United States - Yoko Niimi; Charles Horioka (Osaka University, Institute of Social and Economic Research (ISER), 2016)
To help shed light on the implications of intergenerational transfers for wealth inequality, this paper examines whether or not individuals who receive intergenerational transfers from their parents are more likely to leave bequests to their children than those who do not using data for Japan and the United States. The estimation results show that the receipt of intergenerational transfers from parents and/or parents-in-law increases the likelihood of individuals' leaving bequests to their own children in both Japan and the United States, which in turn is likely to contribute to the persistence or widening of wealth disparities. However, such a tendency is found to be stronger among less better-off households in both countries, and this may help alleviate the disequalizing effect of intergenerational transfers on the distribution of wealth, at least to some extent.
Keywords: D10; D31; D64; E21; I24; 330; bequests; education; inheritances; intergenerational transfers; inter vivos transfers; wealth distribution; wealth inequality